NGHIÊN CỨU KHẢ NĂNG ĐÁP ỨNG MIỄN DỊCH VỚI KHÁNG NGUYÊN POLYHEDRIN CỦA MONODON BACULOVIRUS (MBV) TRÊN CHUỘT BALB/c - Giang An, Nguyễn Thị; Hiếu, Đỗ Khắc; Quyền, Đồng Văn; Thảo, Đỗ Thị; Kháng, Đinh Duy (Vietnam Journal of Science and Technology, 2012)
SUMMARY STUDY ON THE IMMUNE RESPONSE OF BALB/c MICE IMMUNIZED WITH NATIVE AND RECOMBINANT POLYHEDRIN OF MONODON BACULOVIRUS (MBV) Monodon baculovirus (MBV) has been considered as a major causative agent in aquaculture industry shrimps and has caused severe losses for shrimp farmers. The recent diagnostic kits for MBV detection were developed based on polyhedrin (polh), the major constituent protein of occlusion bodies of MBV. It has been known that the specificity and sensitivity of the antibodies to polh (anti-polh) is a critical issue for the success of MBV diagnostic kit development. In this study we used native and recombinant polh to immunized BALB/c mice and evaluated the humoral immune response of the mice by characterization of the antibodies against these antigens. Two groups of BALB/c mice (4/each group) were injected with native polh purified from MBV-infected Penaeus monodon and recombinant polh purified from the recombinant E. coli strain, respectively. The Western blot analysis showed that these antibodies reacted specifically to the native polh from MBV-infected Penaeus monodon. The antibody titer of each BALB/c mouse was evaluated by ELISA using purified native polh. Based on ELISA results, the mice with highest antibody titers against the native and recombinant polh were selected. This study provides fundamental data for hybridoma cell lines creation to produce monoclonal antibodies against polh and use for MBV diagnostic kit development. Keyword. Immune response, BALB/c mice, Polyhedrin, Monodon Baculovirus, ELISA, Western blot.